PENYELESAIAN SENGKETA KASUS INVESTASI AMCO VS INDONESIA MELALUI ICSID - Rico Geraldi, Aldo; Astariyani, Ni Luh Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
This writing aims to explain the procedure of the related dispute settlement. It applies normative legal research method combined with statutory, casuistic, and historical approaches. It shall illustrate the settlement ruling, chronological order, and verdict upon the case. Conclusion draw through this writing shall be means of conciliation is regulated pursuant to Chapter III of ICSID Convention and Rules of Procedure for Conciliation Proceedings (Conciliation Rules).
Keywords: Dispute Settlement, Investment, ICSID